Pola penyediaan dan rantai pasok pakan serat pada musim kemarau di peternakan rakyat sapi perah, Lembang, Kabupaten Bandung Barat - Atikah Nur Hamidah; Norma Nuraina; Despal Despal; Epi Taufik (Universitas Sebelas Maret, 2021)
Objective: This study aimed to explore and understand the source of fiber feed that is commonly used, and analyze the activities of fiber feed provision in dairy farms during the dry season, and investigate the fiber feed supply chain.Methods: This research was conducted on rural dairy farms in the Sub-district of Lembang located in West Bandung District. The data was collected by adopting an interview method with 50 farmers implements a purposive sampling technique to gather information regarding the provision pattern, supply chain of respective fibre feed. Samples of fiber feed in the dairy farms were taken using a simple random sampling technique. The data acquired is analyzed using descriptive analysis; these data consist of nutrient content of the fiber feed, provision pattern during the dry season, and the supply chain map of those fiber feed provisions.Results: The result reveals that the fiber feed that has been given to the dairy cows was cultivated grass, natural grass, legumes, and plant residue that entirely supplied from neighborhood area (≤ 30 km), which has different nutrient content. There are 16 provision patterns of fibre feed in the dry season, the vast majority of provision pattern was the combination of foraging from the farmer’s land and feed purchasing. By referring to the RFV calculations, legumes and vegetable waste have good quality. The fibre feed supply chain is relatively short, which is about (1-4 actors) due to its freshness and required no processing.Conclusions: In conclusions, the fibre feed that has been given to the dairy cows was cultivated grass, natural grass, legumes, and plant residue. There are 16 provision patterns of fibre feed in the dry season. The fibre feed supply chain is relatively short.